2018
DOI: 10.1002/eap.1829
|View full text |Cite
|
Sign up to set email alerts
|

Black walnut alley cropping is economically competitive with row crops in the MidwestUSA

Abstract: The maize–soybean rotation (MSR) dominates the Midwest United States and degrades many ecological functions. Black walnut (Juglans nigra L.) plantation forestry (PF) and alley cropping (AC) are two alternative land‐uses that can enhance productivity and restore ecosystem services. Given the lack of robust market mechanisms to monetize ecosystems services, we tested whether the profitability of PF and AC could drive adoption in the Midwest. Publically available data on black walnut soil suitability, timber pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…According to Wolz and DeLucia (2019), alley cropping has shown great potential as a scalable agricultural alternative that can enhance production while simultaneously improving sustainability in the Midwest United States. Our results from alley cropping in the humid tropics of Amazonian periphery also showed that the biomass of Gliricidia had a positive effect on soil improvement and nitrogen uptake, thereby contributing to agricultural intensification by increasing maize grain yield by 3.5 tons/ha.…”
Section: Use Of Nitrogen and Maize Grain Yieldmentioning
confidence: 99%
“…According to Wolz and DeLucia (2019), alley cropping has shown great potential as a scalable agricultural alternative that can enhance production while simultaneously improving sustainability in the Midwest United States. Our results from alley cropping in the humid tropics of Amazonian periphery also showed that the biomass of Gliricidia had a positive effect on soil improvement and nitrogen uptake, thereby contributing to agricultural intensification by increasing maize grain yield by 3.5 tons/ha.…”
Section: Use Of Nitrogen and Maize Grain Yieldmentioning
confidence: 99%
“…Spatial mapping and economic analysis have demonstrated improvement of farm-level profitability through targeted subfield cultivation of perennial grasses, switchgrass (Panicum virgatum), and miscanthus (Miscanthus giganteus), in place of low-yielding maize and soybean [4,5]. A recent study by Wolz and DeLucia [6] utilized similar spatial mapping of timber-based black walnut (Juglans nigra) plantations and alley cropping systems to demonstrate increased profitability through targeted system placement. Across four states in the Midwest U.S., this study showed that black walnut alley cropping systems could increase profitability for landowners on 23.4% of cultivated land, assuming a 5% discount rate in future yields [6].…”
Section: Finding a Place For Tree Crops In The Midwest Usmentioning
confidence: 99%
“…A recent study by Wolz and DeLucia [6] utilized similar spatial mapping of timber-based black walnut (Juglans nigra) plantations and alley cropping systems to demonstrate increased profitability through targeted system placement. Across four states in the Midwest U.S., this study showed that black walnut alley cropping systems could increase profitability for landowners on 23.4% of cultivated land, assuming a 5% discount rate in future yields [6]. In effect, the studies by Brandes et al [4,5] and Wolz and DeLucia [6] provide evidence for considering the targeted integration of other low-input perennials, which extends to a growing number of tree crop species.…”
Section: Finding a Place For Tree Crops In The Midwest Usmentioning
confidence: 99%
See 2 more Smart Citations